2022
DOI: 10.5194/amt-15-7337-2022
|View full text |Cite
|
Sign up to set email alerts
|

Improving continuous-flow analysis of triple oxygen isotopes in ice cores: insights from replicate measurements

Abstract: Abstract. Stable water isotope measurements from polar ice cores provide high-resolution information about past hydrologic conditions and are therefore important for understanding earth's climate system. Routine high-resolution measurements of δ18O, δD, and deuterium excess are made by continuous-flow analysis (CFA) methods that include laser spectrometers. Cavity ring-down laser spectroscopy (CRDS) allows for simultaneous measurements of all stable water isotopes, including δ17O and 17O excess (Δ17O); however… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…daily) data calibration against multiple reference waters, adopting a new calibration method that utilizes more reference water measurements than typical crDS strategies. Davidge et al (2022) demonstrated that cFA-crDS for ∆ 17 O performs as well as discrete methods by measuring replicate sections of an ice core from Greenland; annually resolved data from that study are provided in Figure 1c-d. they also found that, though small, the greatest source of uncertainty for ∆ 17 O by cFA-crDS is the calibration technique.…”
Section: Lindsey Davidgementioning
confidence: 84%
See 2 more Smart Citations
“…daily) data calibration against multiple reference waters, adopting a new calibration method that utilizes more reference water measurements than typical crDS strategies. Davidge et al (2022) demonstrated that cFA-crDS for ∆ 17 O performs as well as discrete methods by measuring replicate sections of an ice core from Greenland; annually resolved data from that study are provided in Figure 1c-d. they also found that, though small, the greatest source of uncertainty for ∆ 17 O by cFA-crDS is the calibration technique.…”
Section: Lindsey Davidgementioning
confidence: 84%
“…Emanuelsson et al 2015). recent work (Davidge et al 2022;Steig et al 2021) demonstrates that cFA-crDS for all stable water isotopes can greatly reduce the analysis time for ∆ 17 O and it can therefore improve the time resolution of ∆ 17 O measurements. cFA-crDS methods will be useful for improving the temporal and spatial resolution of ∆ 17 O to characterize the natural variability of meteoric ∆ 17 O. recent work demonstrates that cFA-crDS for ∆ 17 O can indeed improve the resolution of ∆ 17 O observations with high precision (<10 per meg), especially when cFA for ∆ 17 O is developed with specific attention to calibration strategies (Davidge et al 2022;Steig et al 2021).…”
Section: Lindsey Davidgementioning
confidence: 99%
See 1 more Smart Citation
“…The system developed by Gkinis et al (2011) used a combination of a peristaltic pump and tuned back-pressure to push water through a silica capillary into a micro-Tee heated to 170 deg C. A similar system has also been deployed and used for calibration of water vapor isotope measurements (Benetti et al, 2017;Steen-Larsen et al, 2014). This system has also shown to be reliable for 17O-excess measurements in continuous-flow analysis of ice core samples (Davidge et al, 2022).…”
mentioning
confidence: 99%